Parental perception of childhood vaccination through focused group discussion approach amongst women in Karnataka, India - Holyachi, Sharankumar; Kengnal, Prakash R; Kumar, Ashok (National Journal of Community Medicine, 2018)
Background: Although India is one of the global producers and exporters of vaccines, the country is still home to about one-third of the world’s unimmunised children. In the current study we conduct a qualitative analysis using focused group discussions in an attempt to uncover the reasons that argue against parental vaccination of children. Methodology: All antenatal and postnatal women coming to the Primary Health Centres (PHC), of a Medical College in Karnataka, India, were approached and informed about the objectives of the study. Written informed consent was obtained subsequent to which FGD’s were conducted in the PHC premises on every Thursday, over a period of two months. Qualitative information received from the women regarding perceptions on immunisation are presented verbatim after translating into English. Data was entered and analyzed using Microsoft Excel 2010. Results: A total of ten FGD’s were conducted in this study. Non-availability of a male member for accompanying them to the immunisation clinics; taking time off from household chores; perceived risks of contracting disease, vaccine side effects; prior negative experience with vaccination, and social environment were cited as barriers against vaccination. Conclusions: This study emphasises the importance of gathering information from parents in order to overcome barriers against vaccinations so as to improve coverage.